Study the chance of respiratory aspiration in intermittent bolus tube feeding in ‎ICU and Trauma ward patients - Somayeh Mosazadeh; Tahereh Khaleghdoost Mohammadi; Farideh Hasavari; Ehsan Kazem Nejad Leili (Guilan University of Medical Sciences, 2011)
Introduction: Bowel feeding is an effective and safe method for patients who are admitted to ‎intensive care wards but despite its many benefits has side effects such as respiratory ‎aspiration. Pneumonia caused by aspiration is responsible for ‎‏15-20%‏‎ of hospital infections, ‎‏24%‏‎ increase in length of hospitalization, and ‎‏39%‏‎ increase of expenses. It is one of the ten ‎reasons of death in USA that can be prevented by appropriate method of feeding. ‎ Objective: This study aims to determine the chance of respiratory aspiration in intermittent ‎bolus tube feeding in patients admitted to ICU and trauma wards.‎ Methods: In this quasi- experimental study ‎‏36‏‎ patients admitted to ICU and trauma wards ‎were fed by intermittent tube bolus method, for ‎‏3‏‎ days. Each time ‎‏150-300‏cc food liquid was ‎administered for ‎‏7‏‎ times a day every ‎‏3‏‎ hours to patients with a ‎‏60‏‎ cc syringe in ‎‏10-15‏‎ minutes. ‎In order to measure the respiratory aspiration, ‎‏0.5‏‎ cc methylen blue ‎‏1%‏‎ was added to ‎‏500‏‎ cc ‎of each meal. In case of patient's need for suction, when the blue color of methylen blue was ‎observed in patients secretion they appeared to have respiratory aspiration.‎ Results: Data analysis showed that respiratory aspiration occurrence in bolus method was ‎‏5.6%‏‎. ‎ Conclusion: According to results, it is obvious that bolus method as mentioned in texts is still ‎the standard method and risk of respiratory aspiration decreases if it is used properly. ‎